A Homobivalent SPECT Radioligand ‐ Serinol Appended Methoxyphenyl Piperazine Derivative for Serotonin Receptor Imaging. Issue 23 (16th June 2021) - Rangaswamy, Sandhya; Saklani, Meenakshi; Kumar, Rajnish; Mathur, Rashi; Kaul, Ankur; Tiwari, Anjani K.; Kaur‐Ghuman, Sandeep; Mishra, Anil K.; Varshney, Raunak
Abstract: Serotonin receptor subtypes are predominantly accountable for various neurophysiologic and cognitive processes and are expressed in the hippocampus region. SPECT based radioligands offer a cost effective understanding to the molecular changes which are used in the diagnoses of various neurological disorders. A Homobivalent approach was used to synthesize 1‐(2‐methoxyphenyl) piperazine based ligand by using click chemistry to incorporate two moieties of MPP via a linker (serinol) for SPECT (Single Photon Emission Computerised Tomography) evaluation. Molecular docking studies show better affinity for radiolabeled DO3 A‐serinol‐bis‐MPP complex. The radiolabeling efficiency of conjugate was optimized and evaluated for stability by various parameters and was found to be 99 %. The complex shows appreciable brain uptake in rabbit. Ex Vivo pharmacology indicated approximately 50 % of the total brain uptake in the hippocampus region which showed the selective preference of the ligand for serotonin receptor. This study could be considered as a novel, informative and preclinical finding for using the synthesised 99m Tc‐DO3 A‐serinol‐bis‐MPP ligand to target serotonin receptor by SPECT imaging. Abstract : DO3 A‐Bis‐MPP for Serotonin receptor was synthesized using bifunctional chelating approach through the click chemistry in good yield. The bivalent compound was evaluated in vitro/in vivo for imaging of serotonin receptor in brain. Invitro toxicity was assessed by MTT assay. The 50 % of total brain uptake observed in the hippocampus region at 5 min shows selective preference of the synthesized conjugate for serotonin‐rich region. The mapping of serotonin receptor with specific imaging probes could help in early intervention in neurophysiologic disorder.